2014
DOI: 10.1002/prep.201300183
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Perchlorate, Friend or Foe? Part 1: The Influence of this Oxidizer on the Aging Behavior of Propellant Compositions

Abstract: Propellants containing nitroglycerine and ammonium perchlorate have been reported to have comparatively shorter shelf lives than analogous energetic materials without this oxidizer. However, investigation into the aging behavior of three compositions containing polyethylene glycol and nitroglycerine revealed that the propellant which included ammonium perchlorate degraded at a slower rate compared with the other materials. It was suggested that ammonium perchlorate might act as an oxygen inhibitor reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In part 1 of this paper it was demonstrated that a propellant composition containing AP along with NG and PEG degraded at a slower rate than the other two materials studied which did not incorporate this oxidizer [1]. The reasons for these observations have been further investigated using a range of analytical techniques.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In part 1 of this paper it was demonstrated that a propellant composition containing AP along with NG and PEG degraded at a slower rate than the other two materials studied which did not incorporate this oxidizer [1]. The reasons for these observations have been further investigated using a range of analytical techniques.…”
Section: Introductionmentioning
confidence: 93%
“…At elevated temperatures, or at lower temperatures such as 80 8C over long time periods, a propellant composition, containing polyethylene glycol (PEG), AP and nitroglycerine (NG), suddenly and violently ignites without prior warning such as a gradual temperature rise or the evolution of brown fumes [1].…”
Section: Introductionmentioning
confidence: 99%